Perancangan Sistem Informasi Akademik Berbasis Web Mobile pada Pondok Pesantren Dar El Amir dengan Metode Waterfall - Setiawan, Andrey Gustaph; Zailani, Achmad Udin (Program Studi Teknik Informatika Universitas Pamulang, 2022)
Dar El-Amir Islamic Boarding School is an Islamic boarding school that has been established since 2008 with a total of 140 students over time, a problem arose. Problems that are often encountered are related to the management of student data, teacher data, employee data, homeroom data and report cards which are still conventional, namely by writing using this paper, it can result in the emergence of larger duplicate data and damage to good data such as blurry writing or missing data. To solve these problems, an integrated academic information system must be made in order to facilitate data management and can be web mobile, meaning that it can be used on any device such as a laptop or mobile phone. This study uses the waterfall technique, this technique can be interpreted like a waterfall because there are stages that must be passed. The effect of studies that have been carried out by applying the waterfall technique shows that this academic information system can be useful for the management of student data, teacher data, tu staff data, homeroom data and report cards so as to make the data management process faster, more efficient and effective and help in the process dissemination of information related to the academic activities of Islamic boarding schools.